Implementasi Nilai – Nilai Karakter Dalam Kegiatan Pengembangan Diri Siswa Di SMP Taruna Dra. Zulaeha Leces Kabupaten Probolinggo - Fiana Agustin; Uswatun Hasanah; Ribut Prastiwi Sriwijayanti (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This study aims to describe the implementation of character values ​​in student self-development activities at SMP Taruna Dra. Zulaeha Lecess, Probolinggo Regency. The research method uses a descriptive qualitative approach. The data in this study were obtained through observation, interviews and documentation. After this data is collected, then qualitative data analysis is carried out. The results of the research show that character values ​​in the self-development of students at SMP Taruna Dra.Zulaeha Leces have been going well. It has been shown that there are a number of students who have achieved a lot of character values ​​in self-development activities through self-development talents achieved by students at schools, both at the Problnggo Regency level, the East Java Province level and even at the National level during 2022. The vice-student teacher has giving encouragement to students in student self-development activities, providing guidance to students in developing achievements, rewarding students who have succeeded in developing achievements. There are several students who do not know about Student Self-Development at SMP Taruna Dra.Zulaeha Leces, namely the student named Zafira Yuri Wardani. With the encouragement and enthusiasm of the teachers, Zafira Yuri Wardani succeeded in participating in self-development activities at school. Zafira Wardani succeeded in getting achievements from the English Club at the Probolinggo Regency level.